2011
DOI: 10.1002/er.1822
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis of the effects of hydrogen addition on methane combustion

Abstract: SUMMARY This paper presents gas emissions from turbulent chemical flow inside a model combustor, for different blending ratios of hydrogen–methane composite fuels. Gas emissions such as CO and O2 from the combustion reaction were obtained using a gas analyzer. NOx emissions were measured with a NOx analyzer. The previously obtained flame temperature distributions were also presented. As the amount of hydrogen in the mixture increases, more hydrogen is involved in the combustion reaction, and more heat is relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(8 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…One study measured CO emission at different axial locations along the combustor. The results indicated that the higher H 2 molar fraction in the fuel blends could benefit a lower CO concentration at a fixed power [14]. Another study showed that adding H 2 molar fraction in the fuel blends with constant fuel volume flow, the CO emission first decreased and then increased [15].…”
Section: Introductionmentioning
confidence: 93%
“…One study measured CO emission at different axial locations along the combustor. The results indicated that the higher H 2 molar fraction in the fuel blends could benefit a lower CO concentration at a fixed power [14]. Another study showed that adding H 2 molar fraction in the fuel blends with constant fuel volume flow, the CO emission first decreased and then increased [15].…”
Section: Introductionmentioning
confidence: 93%
“…Results showed that hydrogen might be considered a good alternative fuel for burners as its reduction of pollutant emissions. Furthermore, İlbaş et al [24] also studied the effects of hydrogen addition on methane combustion in nature gas burner. The authors concluded that combustion efficiency increased and CO emission decreased as the hydrogen content increased in the blending fuel, and hydrogen-methane blending fuels were efficiently used without any significant modification in the natural gas burner [24].…”
Section: Introductionmentioning
confidence: 99%
“…In Figure 11C, as the hydrogen content increases, the NO-production rate increases when the mixture fraction is between 0.1 and 0.2, where the combustion occurs. The tendency of the NO production to increase with the increase in hydrogen content was also demonstrated in the results obtained by _ Ilbas ¸et al 47 and Park et al 48 Through their research, they pointed to an increase in the flame temperature as the major parameter for the increase in NO production. In pressurized methane-oxy combustion, when hydrogen is blended, it is necessary to analyze the chemical reactions involved in the formation of NO at 1 and 30 atm separately.…”
Section: Effect Of Hydrogen On the Unpurified Natural Gasmentioning
confidence: 63%